1987
DOI: 10.1111/j.1651-2227.1987.tb10556.x
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Discharge after Hospital Birth: Breastfeeding

Abstract: Breastfeeding was studied among women discharged early and late after normal delivery in a hospital. Early discharge was defined as leaving the hospital 24-48 h after delivery in combination with domiciliary visits, and late discharge as the regular hospital postpartum care (mean 6 days). 164 women interested in participating in the early discharge study were randomly allocated in late pregnancy to a group offered early discharge (Experimental group = EG) or a group offered the traditional later discharge (Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 5 publications
0
44
0
1
Order By: Relevance
“…5,28,29 There have been studies that suggested that breastfeeding success was increased in women discharged earlier with optimal support. [11][12][13][14] The selective population of this study, as well as the fact that Ͼ70% of the women received a home visit, may explain some of the differences between our study and others.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…5,28,29 There have been studies that suggested that breastfeeding success was increased in women discharged earlier with optimal support. [11][12][13][14] The selective population of this study, as well as the fact that Ͼ70% of the women received a home visit, may explain some of the differences between our study and others.…”
Section: Discussionmentioning
confidence: 75%
“…4,8 -10 However, other studies from the early 1960s and from Europe have presented evidence suggesting that prompt discharge to home may allow earlier establishment of an adequate milk supply and less supplementation. [11][12][13][14] Factors that affect breastfeeding success have been examined extensively, primarily in the nursing literature. 5,[15][16][17] However, the impact of the health care delivery system, both in the hospital and after discharge, on breastfeeding success has been less well documented.…”
mentioning
confidence: 99%
“…Longer hospital stays were associated with lower breastfeeding rates among Arabs only. Longer hospital stays have been associated with a higher use of supplementary feeds 23 and a negative impact on breastfeeding. 24 Although it is not clear why this effect is seen only in the Arab group, the results identify these mothers as a higher risk group that could benefit from follow-up in the early postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Early discharge from hospital and home visits by midwives was introduced in Sweden in 1984 (14). Since the early 1990s our clinic has aimed to distinguish between healthy women and children after delivery, and women and children in need of hospital care in order to provide the most appropriate postnatal care.…”
Section: Introductionmentioning
confidence: 99%